HUBUNGAN FAKTOR SOSIAL EKONOMI, HIGIENE SANITASI LINGKUNGAN, TINGKAT KONSUMSI, DAN KEJADIAN INFEKSI DENGAN STATUS GIZI ANAK USIA 2-5 TAHUN DI DESA TUBLOPO TAHUN 2014 - Hetty Gustina Simamora (Elisabeth Health Jurnal, 2017)
he existence of multidimensional crisis has menurnkan nutritional status of society. one of the community groups that are susceptible to the decline of nutritional status of children aged 2-5 years, because at this age the child was not getting milk while the food consumed has not been sufficient to meet the growing nutritional needs. Nutritional status is indirectly related to socioeconomic factors, sanitation hygiene, consumption level and the incidence of infection. Method : This research is an observational study with survey method and desaim cross sectional. Samples are children aged 2-5 Years residing in the village Tublopo. The sample size is 76 children taken proportionally. Respondents were mothers of the sample. The statistical test used is Rank Spearman and Chi-Square. Result : Respondents came from low socio economic groups with low knowledge of nutrition, 93.4% energy consumption level, sample including deficit and protein consumption rate of 35.5% sample including deficit. In the last three months and at the time of the study, 63.2% of the samples had upper respiratory tract infection (ISPA) and 1.3% of samples suffering from diarrhea, 39.6% of the samples had nutritional status of ARI occurrence related to ZBB / U score in child age 2-5 years. The level of education of the mother is related to the level of energy and protein consumption. Conclusion: To anticipate the improvement of malnutrition status, it is suggested to the community, especially the mothers who have not fulfilled their obligation to learn 9 years to participate in the C package program and for TTU District Health Office to provide interesting counseling